Perancangan game horror puzzle “The Hidden Surah" dengan implementasi Finite State Machine pada NPC untuk media edukasi Surat An-Nas - putri, dwi andina; Diana, Nirma Nur; Febriananto, Nur Muhammad Anang; Zaiba, Azmi Fash Shalna (Maliki Interdisciplinary Journal, 2026)
Qur’anic education, especially the memorization of short surahs, often relies on conventional methods that are less engaging for young learners. Game technology can serve as an interactive and enjoyable learning medium. This study developed an Islamic-themed horror puzzle game titled “The Hidden Surah” as an educational tool for learning Surah An-Nas using the Finite State Machine (FSM) method for Non-Player Character (NPC) behavior. The game was built with Unity Engine and programmed in C#. FSM was applied to four enemy NPCs Pocong, Kuntilanak, Tuyul, and Genderuwo with distinct state transitions responding to player actions. A maze system was also implemented to enhance exploration and challenge. Internal black box testing confirmed all core features functioned properly with a 100% success rate. The game integrates Islamic values by emphasizing that Qur’anic recitation and dzikr act as spiritual protection from darkness. Thus, The Hidden Surah has the potential to become an alternative learning medium that is interactive, educational, and has spiritual value.